Una scuola inclusiva Azioni per contrastare i rischi di dispersione di alunne e alunni di origine straniera - Filosa, Giovanna; Gamberoni, Emanuela (Tratti geografici, 2023)
This volume concerns the role of the Italian schools, the associations and their actors to counteract educational dispersion and encourage the inclusion of minors with a migratory background. The work is part of a collaboration project between Inapp (National Institute for Public Policy Analysis) and Aiig (Italian Association of Geography Teachers) aimed to map the "Analysis, training and territorial activities for preventing/countering the risks of educational dispersion of young people with a migratory background" (June 2022 - March 2023). This collaboration stems from a program agreement between Inapp and Ministry of Labor and Social Policies - General Directorate of Immigration, on "Citizen Integration Policies of Third Countries". The first part, focused on theoretical aspects, develops the idea of a school as welcoming community, in which disciplines such as geography and tools such as digital teaching can be significant resources to draw on. Related to this, a specific focus on the socio-cultural development in the border and internal areas is underlined. The second part collects the empirical evidences emerging from some territorial laboratories and training courses organized by Inapp and Aiig in various Italian regions. These evidences represent the main results of a qualitative survey on risks of educational dropout of young people with a migratory background. A wealth of proposals together with successful and critical factors is unraveled. In the last section of the volume, these various and original practices are reported by teachers, school managers, and operators, representatives of voluntary organisations, associations and third sector. The idea was to carry out the research not on the actors of inclusion, but with them, giving voice to their experiences. It was a sort of an ideal journey from the north of Italy, where the presence of students with a migratory background is higher, to the south, considered the land of their arrival and transit.